2001
DOI: 10.1002/chin.200127072
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of ω‐Substituted Alkanethiols and (Bromomethyl)methylthiomalonates.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…We synthesized the molecules shown in Figure 1 following reported procedures (for details see Supporting Information). 62,63 For the formation of SAMs, we followed a procedure of the type we currently use and have described elsewhere in detail. 24 We chose to use Ag TS for the majority of our work, rather than Au TS , because it allows direct comparison with some of the data that have already been reported (the data from Yoon et al, Nijhuis et al, and us were all reported on Ag TS ; those by Cahen used a related but different junction).…”
Section: Resultsmentioning
confidence: 99%
“…We synthesized the molecules shown in Figure 1 following reported procedures (for details see Supporting Information). 62,63 For the formation of SAMs, we followed a procedure of the type we currently use and have described elsewhere in detail. 24 We chose to use Ag TS for the majority of our work, rather than Au TS , because it allows direct comparison with some of the data that have already been reported (the data from Yoon et al, Nijhuis et al, and us were all reported on Ag TS ; those by Cahen used a related but different junction).…”
Section: Resultsmentioning
confidence: 99%
“…Following identical sequence, indoles 9b – l were transformed into disulfides 4b – l using either cystamine 13a or amines 13b – g (Scheme , Table ), some of which were synthesized using the general methodology described by Pfammatter . Deprotection of the silyl ether of 14r took place concomitantly with trityl deprotection.…”
Section: Design and Synthesismentioning
confidence: 99%